Construction of stability domains for linear differential equations with delay - Klevchuk, I.I.; Hrytchuk, M.V. (SWorldJournal, 2023)
The aim of the present article is to investigate of solutions stability of linear autonomous differential equations with retarded argument. It is obtained the necessary and sufficient conditions, for all the roots of the characteristic equation to have negative real part. We investigate the boundedness conditions and construct a domain of stability for linear autonomous differential equation with several delays. We use D-partition method, argument principle and numerical methods to construct of stability domains.
ПОБУДОВА ОБЛАСТЕЙ СТІЙКОСТІ ЛІНІЙНИХ ДИФЕРЕНЦІАЛЬНИХ РІВНЯНЬ ІЗ ЗАПІЗНЕННЯМ
The aim of the present article is to investigate of solutions stability of linear autonomous differential equations with retarded argument. It is obtained the necessary and sufficient conditions, for all the roots of the characteristic equation to have negative real part. We investigate the boundedness conditions and construct a domain of stability for linear autonomous differential equation with several delays. We use D-partition method, argument principle and numerical methods to construct of stability domains.
Keywords: delay differential equation, stability domain, argument principle, D-partition